2017
DOI: 10.1111/imr.12562
|View full text |Cite
|
Sign up to set email alerts
|

Development of allergic immunity in early life

Abstract: The growth and maturity of the peripheral immune system and subsequent development of pulmonary immunity in early life is dictated by host, environmental and microbial factors. Dysregulation during the critical window of immune development in the postnatal years results in disease which impacts on lifelong lung health. Asthma is a common disease in childhood and is often preceded by wheezing illnesses during the preschool years. However, the mechanisms underlying development of wheeze and how and why only some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 161 publications
(328 reference statements)
0
33
0
1
Order By: Relevance
“…Virus infection can both promote the development of airway inflammation and exacerbation in asthmatic patients. Respiratory sincital virus (RSV) infection is common in children under 2 years old and is associated with asthma development later in life . RSV infection was shown to induce IL‐13‐producing ILC2s in neonatal but not adult mice through epithelial‐derived IL‐25 production, resulting in mucus production and airway responsiveness .…”
Section: Implications Of Memory Ilc2s In Asthmamentioning
confidence: 99%
“…Virus infection can both promote the development of airway inflammation and exacerbation in asthmatic patients. Respiratory sincital virus (RSV) infection is common in children under 2 years old and is associated with asthma development later in life . RSV infection was shown to induce IL‐13‐producing ILC2s in neonatal but not adult mice through epithelial‐derived IL‐25 production, resulting in mucus production and airway responsiveness .…”
Section: Implications Of Memory Ilc2s In Asthmamentioning
confidence: 99%
“…Early life represents a critical window for immune development. During this period, a variety of environmental factors, such as pet exposure, encountered by infants determine health or allergic diseases (33). Several protective mechanisms of early life pet exposure had been summarized as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine balance during early life, which could be influenced by external factors, is critical in the development of allergic response (30). In addition, recent studies attempting to correlate genetic variations in Toll-like receptors (TLRs) and CD14 genes with atopic disease supported the existence of a gene-environment interaction, although the results were conflicting (5,10,33). However, research by Swedish BAMSE presented that the observed protective effect of dog exposure may be partly due to selective dog avoidance by families with parental atopic dermatitis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Allergic inflammation appears to be a systemic disease, but certain tissues such as the upper and lower airways, the gastrointestinal tract, and the skin are affected. The term “Allergic march” refers to the sequential development of allergic inflammation in children: atopic dermatitis often accompanied by eczema precedes the onset of other allergic diseases, including allergic asthma and allergic rhinitis . In addition, some patients suffer from two or three of these diseases together, even as adults.…”
mentioning
confidence: 99%
“…The term "Allergic march" refers to the sequential development of allergic inflammation in children: atopic dermatitis often accompanied by eczema precedes the onset of other allergic diseases, including allergic asthma and allergic rhinitis. 26,27 In This article introduces a series of reviews covering Allergic Inflammation appearing in Volume 278 of Immunological Reviews. F I G U R E 1 (A) Cellular and molecular interaction in the pathogenesis of allergic airway inflammation, sensitization, and acute phase.…”
mentioning
confidence: 99%